Experimental and kinetic analysis of hydrothermal aging effects on ammonia adsorption capacity over a commercial Cu-zeolite selective catalytic reduction catalyst. (October 2019) - Wang, Tae Joong; Im, In Hyuk
Ammonia/urea selective catalytic reduction is an efficient technology to control NOx emission from diesel engines. One of its critical challenges is the performance degradation of selective catalytic reduction catalysts due to the hydrothermal aging experienced in real-world operations during the lifetime. In this study, hydrothermal aging effects on the reduction of ammonia adsorption capacity over a commercial Cu-zeolite selective catalytic reduction catalyst were investigated under actual engine exhaust conditions. Ammonia adsorption site densities of the selective catalytic reduction catalysts aged at two different temperatures of 750°C and 850°C for 25 h with 10% H2 O were experimentally measured and compared to that of fresh catalyst on a dynamometer test bench with a heavy-duty diesel engine. The test results revealed that hydrothermal aging significantly decreased the ammonia adsorption capacity of the current commercial Cu-zeolite selective catalytic reduction catalyst. Hydrothermal treatment at 750°C reduced the ammonia adsorption site to 62.5% level of that of fresh catalyst, while hydrothermal treatment at 850°C lowered the adsorption site to 37.0% level of that of fresh catalyst. Also, in this study, numerical simulation and kinetic analysis were carried out to quantify the impact of hydrothermal aging on the reduction of ammonia adsorption capacity by introducing an aging coefficient. The kinetic parameter calibrations based on actual diesel engine tests with a commercial monolith Cu-zeolite selective catalytic reduction catalyst provided a highly realistic kinetic parameter set of ammonia adsorption/desorption and enabled a mathematical description of hydrothermal aging effect.